Knowledge, attitude and practice of screening for carcinoma of the cervix among reproductive health clients at three teaching hospitals, Addis Ababa, Ethiopia - Terefe, Yifru; Gaym, Ashebir (Ethiopian Journal of Reproductive Health, 2018)
Abstract Background: Carcinoma of the cervix is one of the commonest cancers of women. It represents about 12%of all cancers in females, and more than half of them die from it. There are clear evidences that cytological screening programs are effective in reducing morbidity and mortality from the disease. Cancer prevention consciousness in developing countries is low and most patients seek consultation only at advanced stages. Objective: This survey was undertaken to elicit information on the knowledge attitude and practice (KAP) of screening for carcinoma of the cervix (Pap smear) among reproductive health (RH) client a at three teaching hospitals in Addis Ababa, Ethiopia: Tikur Anbessa, St Paul’s and Ghandi Memorial. Method: - Across sectional descriptive KAP study was conducted on 276 RH clients attending emergency and regular outpatient department (OPD) antenatal, postnatal, family planning and referral clinics at the three hospitals. A structured pre-tested questionnaire was prepared and the respondents were interviewed by the principal investigator. Results: Most respondent (81.2%) had never heard of Pap smear screening. The source of information for those who had heard about this test were health institutions for 65.4% of the respondents. Women who had heard about Pap smear screening were younger than those who had never heard of it. Only 6.5 % of all the respondent had ever had a Pap smear test. The reasons given for not having the test were: no gynecologic symptoms (41.2%); don’t know the place were it was done (32.4%); wait till older (14.7%). And consider it was not important (11.8%). For those who had ever had the test, the indication for undergoing the test were doctor / nurse consultation (72.2%)and personal initiative (20.7%). Women who had a Pap smear test had higher level of education than those who never had a Pap smear. Almost all the respondents were willing to undergo the screening test in the future. Conclusion: The awareness and practice of the screening procedure of cervical cancer (Pap smear) among RH clients in Addis Ababa is very low. There is a need for intensifying health education provision on cervical cancer screening in the city. Keywords: Cervical cancer screening Pap smear, KAP on cervical cancer